2016
DOI: 10.1016/j.automatica.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Mean and variance of the LQG cost function

Abstract: Linear Quadratic Gaussian (LQG) systems are well-understood and methods to minimize the expected cost are readily available. Less is known about the statistical properties of the resulting cost function. The contribution of this paper is a set of analytic expressions for the mean and variance of the LQG cost function. These expressions are derived using two different methods, one using solutions to Lyapunov equations and the other using only matrix exponentials. Both the discounted and the non-discounted cost … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Our goal is to choose F α and K α so as to minimize the expected cost J. This cost, according to [3,Theorem 2], equals…”
Section: Optimizing the Discounted Cost Functionmentioning
confidence: 99%
“…Our goal is to choose F α and K α so as to minimize the expected cost J. This cost, according to [3,Theorem 2], equals…”
Section: Optimizing the Discounted Cost Functionmentioning
confidence: 99%
“…Usually, the expected value of the cost function is minimized, however, there are also approaches that consider variance such as minimum variance control (see [1] for details). Closed form solutions for the variance of the cost were derived very recently in [15]. Taking this approach one step further, we consider the full distribution of the cost functional.…”
Section: Model-based Design Model Learningmentioning
confidence: 99%
“…It is shown that the discounted-cost linear quadratic regulator can not only achieve the prescribed optimization index, but also guarantees the exponential stable of the optimal control system [1]. Therefore, the the discounted-cost linear quadratic regulation problem has attracted increasing attention in recent years, especial for non-switched systems [3,4]. For the linear quadratic Gaussian systems, [4] presented a set of analytic expressions for the mean and variance of the discounted-cost function by Lyapunov equations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the the discounted-cost linear quadratic regulation problem has attracted increasing attention in recent years, especial for non-switched systems [3,4]. For the linear quadratic Gaussian systems, [4] presented a set of analytic expressions for the mean and variance of the discounted-cost function by Lyapunov equations. [3] proposed the optimal controller and observer gains for a class of the linear quadratic Gaussian systems by solving the Riccati equation.…”
Section: Introductionmentioning
confidence: 99%